Turismo rural comunitario: una alternativa para el desarrollo socioeconómico de la comunidad El Ostional, San Juan del Sur, Rivas, Nicaragua - Arróliga Montenegro, Carmen Anielka (Universidad Nacional Agraria, 2020)
Community-based Rural Tourism is a social and economic alternative to traditional tourism. This study aims to verify if the model of community-based Rural Tourism development applied in the El Ostional community is being managed correctly and thus check if there is an impact on improving the quality of life of the population, promoting the rescue of cultural identity. To know these aspects it is necessary to describe the socioeconomic factors such as organization, gender equity and the role of women, training, community economy and the linkage of tourism with other sources of income and subsequently evaluate its rural community tourism model. For this purpose, the Sentinel Site Surveillance methodology used by the Tropical Disease Research Center was applied that combines quantitative and qualitative methods, using households as the unit of analysis for social variables and sources of income for economic variables. Community Rural Tourism in El Ostional is increasingly important for the municipality of San Juan del Sur, so much so that, the projects of the government and the tourism regulatory entity, have the community identified as the main attraction in order to decongest the influx of tourists to San Juan del Sur. The tourist model of El Ostional allows the generation of socioeconomic benefits directly to the tourism cooperative and indirectly to the rest of the inhabitants.El turismo rural comunitario es una alternativa social y económica al turismo tradicional. Este estudio pretende comprobar si el modelo de desarrollo turístico rural comunitario aplicado en la comunidad El Ostional se está gestionando de manera correcta y comprobar de esta forma si hay impacto en la mejora de la calidad de vida de la población, promoviendo el rescate de la identidad cultural. Para conocer estos aspectos es necesario describir los factores socioeconómicos como organización, equidad de género, y función de la mujer, capacitación, economía comunitaria y la vinculación del turismo con otras fuentes de ingreso y posteriormente evaluar su modelo turístico rural comunitario, para esto se aplicó la metodología de Vigilancia en Sitios Centinela utilizada por el Centro de Investigación de Enfermedades Tropicales que combina métodos cuantitativos y cualitativos, utilizando como unidad de análisis los hogares para las variables sociales y las fuentes de ingresos para variables económicas. El Turismo Rural Comunitario en El Ostional es cada vez más importante para el municipio de San Juan del Sur, tanto que, los proyectos del gobierno y de la entidad reguladora del turismo, tienen a la comunidad identificada como el principal atractivo para así descongestionar la afluencia de turistas a San Juan del Sur. El modelo turístico de El Ostional permite generar beneficios socioeconómicos directamente a la cooperativa de turismo e indirectamente al resto de los pobladores.